Optical-magnetic driven microalgae microneedle patch, preparation method and application thereof
Patent Information
- Application Number
- CN202611183877.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-05
- Publication Date
- 2026-10-13
AI Technical Summary
其二,生物膜的物理屏障阻碍光敏剂的有效渗透,进一步限制了PDT在深部感染中的应用
本发明提供了一种光磁驱动微藻微针贴片的制备方法,包括下列步骤:S1、将乙二醇、六水合氯化镁、六水合氯化铁、尿素、聚乙二醇、聚乙烯吡咯烷酮混合,反应,得到MFO粉末;S2、将MFO粉末与水混合后加至聚乙烯亚胺溶液中,超声,待超声结束后,孵育、离心,得到MP纳米材料;S3、将MP纳米材料与水混合后,得到MP溶液,随后加入小球藻溶液和水,孵育、离心,得到CMP材料;S4、将CMP材料置于透明质酸溶液中,得到CMPH溶液,随后将CMPH溶液加入至微针模具中,依次进行抽真空、浓缩,得到光磁驱动微藻微针贴片。
Smart Images

Figure CN122894302A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of biomedical technology, and in particular to a photomagnetically driven microalgae microneedle patch, its preparation method, and its application. Background Technology
[0002] Drug-resistant bacterial infections of skin and soft tissues in diabetic wounds pose a widespread health risk in the medical, public health, and daily protection fields. Traditional treatments such as antibiotic ointments and silver ion dressings have significant drawbacks. Long-term use can easily induce bacterial resistance, and single-mode bactericidal treatments are insufficient to overcome deep infections, biofilms, and wound hypoxia, resulting in limited therapeutic effects and a high recurrence rate. Furthermore, existing antibacterial products have limited functionality, lacking self-oxygenation and multi-mechanism synergistic design, failing to meet the antibacterial needs of complex infection scenarios. Moreover, diabetic wounds, due to their unique pathological characteristics such as hyperglycemia, hypoxia, bacterial infection, and oxidative stress caused by inflammatory responses, severely hinder wound healing and may even lead to amputation. Therefore, promoting rapid and effective healing of diabetic wounds is a crucial problem that urgently needs to be solved in today's society.
[0003] Traditional methods such as debridement, antibiotics, and ordinary dressings are insufficient to simultaneously break the vicious cycle of wound hypoxia, persistent infection, and excessive oxidative stress, resulting in limited treatment efficacy and a high recurrence rate. In recent years, the integration of minimally invasive photothermal therapy, phototherapy, bioactive carriers, and percutaneous delivery technologies has given rise to a series of multifunctional synergistic repair strategies. Photodynamic therapy (PDT) is an emerging antibacterial strategy. Its basic principle is to use light of a specific wavelength to excite a photosensitizer, transferring energy to surrounding oxygen molecules to generate reactive oxygen species (ROS), thereby destroying bacterial cell structure. PDT has a killing effect on Gram-positive bacteria, Gram-negative bacteria, and biofilms, and due to its multi-target mechanism, it is less likely to induce bacterial resistance. However, traditional PDT antibacterial therapy faces several technical bottlenecks in practical applications. Firstly, PDT is heavily dependent on oxygen; its bactericidal efficiency is directly limited by the local oxygen concentration. The dense structure of the bacterial biofilm at the infection site hinders oxygen diffusion, creating a deeply hypoxic microenvironment, which significantly reduces the efficacy of PDT. Secondly, the physical barrier of biofilms hinders the effective penetration of photosensitizers, further limiting the application of PDT in deep infections.
[0004] Therefore, there is an urgent need to develop a wound repair technology with in-situ autonomous oxygen supply capability and integrated multi-mode synergistic antibacterial mechanism to break through the hypoxic application bottleneck of traditional photodynamic therapy, overcome the permeability barrier of bacterial biofilm, and at the same time, specifically improve the pathological microenvironment of diabetic wounds to meet the clinical treatment needs of drug-resistant bacterial-infected chronic and difficult-to-heal diabetic wounds. Summary of the Invention
[0005] The purpose of this invention is to provide a photomagnetically driven microalgae microneedle patch, its preparation method, and its application. This system leverages the minimally invasive transdermal drug delivery advantages of HA microneedles, integrating the magnetocaloric effect of nanomaterials, multiple enzymes, and photodynamic therapy (PDT) into a triple sterilization mode. Combined with the in-situ oxygen production function of living microalgae, it achieves highly efficient clearance of drug-resistant bacterial infections without the need for antibiotics. Simultaneously, through Mg... 2+ It uses three pathways—slow release, local oxygen enrichment, and lactate degradation—to synergistically regulate B cell and macrophage polarization and reshape the immune microenvironment of the wound, specifically for the repair of chronic, non-healing wounds caused by drug-resistant bacteria in diabetic patients.
[0006] To achieve the above objectives, the present invention provides a method for preparing a photomagnetically driven microalgae microneedle patch, comprising the following steps: S1. Mix ethylene glycol, magnesium chloride hexahydrate, ferric chloride hexahydrate, urea, polyethylene glycol, and polyvinylpyrrolidone, and react to obtain MFO powder; S2. Mix MFO powder with water and add it to a polyethyleneimine solution. Sonicate the mixture. After sonication, incubate and centrifuge to obtain MP nanomaterials. S3. After mixing MP nanomaterials with water, an MP solution is obtained. Then, Chlorella solution and water are added, and the mixture is incubated and centrifuged to obtain CMP material. S4. Place the CMP material in a hyaluronic acid solution to obtain a CMPH solution. Then, add the CMPH solution to a microneedle mold and perform vacuuming and concentration in sequence to obtain a photomagnetically driven microalgae microneedle patch.
[0007] In this invention, the specific mixing process described in S1 includes: first, adding magnesium chloride hexahydrate and ferric chloride hexahydrate to ethylene glycol in sequence, then adding urea and polyethylene glycol in sequence, and finally adding polyvinylpyrrolidone.
[0008] In this invention, the volume molar ratio of ethylene glycol, magnesium chloride hexahydrate, and ferric chloride hexahydrate in S1 is 40 mL: 1.5~1.9 mmol: 4.5~5.5 mmol, preferably 40 mL: 1.7 mmol: 5 mmol; the mass-volume ratio of urea to ethylene glycol is 3~4 g: 40 mL, preferably 3.6 g: 40 mL; the volume ratio of polyethylene glycol to ethylene glycol is 1.5~2.5: 40, preferably 2: 40, and the molecular weight of polyethylene glycol is preferably 400; the mass-volume ratio of polyvinylpyrrolidone to ethylene glycol is 3.5~4.5 g: 40 mL, preferably 4 g: 40 mL.
[0009] In this invention, the temperature of the reaction in S1 is 180~220℃, preferably 200℃, and the time is 6~10h, preferably 8h.
[0010] In this invention, after the reaction described in S1 is completed, the process further includes centrifuging, washing, and drying the reaction system. The centrifugation speed is 8000~12000 rpm, preferably 10000 rpm, and the time is 8~12 min, preferably 10 min; the drying temperature is 55~65℃, preferably 60℃, and the time is 6~10 h, preferably 8 h.
[0011] In this invention, the specific steps in S2 include: mixing MFO powder with water and then sonicating to obtain an MFO powder dispersion; adding the MFO powder dispersion dropwise to a polyethyleneimine solution and sonicating; after sonication, incubating, centrifuging, washing, pre-freezing, and freeze-drying to obtain MP nanomaterials. The centrifugation speed is 160~200 rpm, preferably 180 rpm, the temperature is 36~38℃, preferably 37℃, and the time is 22~26 h, preferably 24 h; the pre-freezing temperature is -85~-75℃, preferably -80℃, and the time is 25~35 min, preferably 30 min; the freeze-drying temperature is preferably -55~57℃, preferably -56℃, the time is preferably 10~14 h, preferably 12 h, and the vacuum degree is preferably 0.05~0.15 Pa, preferably 0.1 Pa.
[0012] In this invention, the polyethyleneimine solution in step S2 is an aqueous solution of polyethyleneimine. This invention does not have special requirements regarding the concentration of the polyethyleneimine aqueous solution; water is used only as a solvent. The mass ratio of MFO powder to polyethyleneimine in step S2 is 1:1~2. The incubation temperature in step S2 is 36~38℃, preferably 37℃, the incubation time is 22~26h, preferably 24h, and the oscillation frequency is 160rpm~200rpm, preferably 180rpm.
[0013] In this invention, the mass fraction of the MP solution in S3 is 200~1000 μg / mL, preferably 800 μg / mL; the OD of the Chlorella solution... 680 The volume ratio of the MP solution to the Chlorella solution is 0.5 to 2.0, preferably 1.0; the volume ratio of the MP solution to the Chlorella solution is 0.5 to 1.5:1, preferably 1:1.
[0014] In this invention, the incubation described in S3 is carried out under light-protected conditions, with a temperature of 36~38℃, preferably 37℃, a time of 55~65min, preferably 60min, and an oscillation frequency of 160~200rpm, preferably 180rpm.
[0015] In this invention, the mass fraction of the hyaluronic acid solution in S4 is 15%~25%, preferably 20%; the volume-to-mass ratio of the hyaluronic acid solution to the CMP material is 1mL:200~1000μg, preferably 1mL:800μg.
[0016] In this invention, the number of vacuuming operations in step S4 is ≥3 times, and the process of a single vacuuming operation is as follows: vacuuming for 0.5~1.5 min and holding for 2.5~3.5 min, preferably vacuuming for 1 min and holding for 3 min; the concentration temperature is 36~38℃, preferably 37℃, and the time is 22~26 h, preferably 24 h; the centrifugation speed is 4600~5000 rpm, preferably 4800 rpm, and the time is 8~12 min, preferably 10 min.
[0017] The present invention also provides a photomagnetically driven microalgae microneedle patch prepared by the above preparation method.
[0018] The present invention also provides the application of the aforementioned photomagnetically driven microalgae microneedle patch in the preparation of medical dressings for treating diabetic wounds.
[0019] The present invention has the following beneficial effects: This invention provides a method for preparing a photomagnetically driven microalgae microneedle patch, comprising the following steps: S1, mixing ethylene glycol, magnesium chloride hexahydrate, ferric chloride hexahydrate, urea, polyethylene glycol, and polyvinylpyrrolidone, reacting to obtain MFO powder; S2, mixing the MFO powder with water and adding it to a polyethyleneimine solution, sonicating, and after sonication, incubating and centrifuging to obtain MP nanomaterials; S3, mixing the MP nanomaterials with water to obtain an MP solution, then adding a Chlorella solution and water, incubating and centrifuging to obtain CMP material; S4, placing the CMP material in a hyaluronic acid solution to obtain a CMPH solution, then adding the CMPH solution to a microneedle mold, and sequentially performing vacuuming and concentration to obtain a photomagnetically driven microalgae microneedle patch.
[0020] This invention is the first to discover MFO powder (MgFe2O) 4-x It possesses microenvironment-responsive MPO-like and LDH-like enzyme activities, which can cause bacterial death due to energy depletion. NADPH-like enzyme activity can disrupt the bacterial redox balance, leading to oxidative damage and death. Furthermore, MgFe2O... 4-x Mg 2+ The release can also participate in chlorophyll synthesis, promote Chl oxygen production, provide an oxygen-rich environment for diabetic wounds, and thus promote PDT to produce ROS.
[0021] MgFe2O 4-x Mg 2+ It releases oxygen through activated anti-inflammatory B cells via the TRPM7 pathway and Chl photosynthetic activity, alleviating hypoxia. Combined with LDH-Like enzyme activity, it can reduce lactate content, induce a decrease in histone lactation levels, activate the AMPK pathway, induce macrophage metabolic reprogramming, and inhibit inflammation.
[0022] This invention uses biocompatible, flexible, and biodegradable hyaluronic acid (HA) as a matrix. The approximately 800μm needle can penetrate the stratum corneum of the skin painlessly, precisely delivering the active ingredients to the site of infection. At the same time, HA constructs a stable three-dimensional network, providing support for the engineered microalgae complex (Chl@MgFe2O4-x-PEI, CMP) and ensuring the stability of its bioactivity.
[0023] The living Chlorella (Chl) in the system is an important oxygen supply unit. Under 660nm laser irradiation, Chl continuously produces oxygen through photosynthesis, which can increase the local dissolved oxygen concentration from 6.5mg / L to 12.8mg / L, effectively improving the hypoxic environment inside the wound and biofilm, and making up for the oxygen raw material gap of PDT.
[0024] MFO powder modified with polyethyleneimine (PEI), namely MP nanomaterials (MgFe2O4-x-PEI), is uniformly dispersed in the system and possesses multiple functional properties. On the one hand, MP nanomaterials exhibit three types of enzyme activity: Nox-Like, MPO-Like, and LDH-Like. Nox-Like enzyme activity consumes intracellular antioxidants in bacteria, dismantling their defense system; MPO-Like enzyme activity catalyzes the generation of strong oxidizing substances, damaging bacterial cell membrane structure; and LDH-Like enzyme activity disrupts bacterial lactate metabolism and blocks energy supply. On the other hand, a 660nm laser can trigger MP nanomaterials to generate hydroxyl radicals (·OH), exerting a PDT killing effect; under an AMF (alternating magnetic field), MP can locally raise the temperature to 45~48℃, directly killing bacteria through magnetothermal stimulation. In addition, heating can optimize catalytic conditions, further improving the catalytic efficiency of the three types of nanoenzymes.
[0025] Under the combined action of laser and AMF, the entire system forms a triple synergistic antibacterial mode of light-magnetism-chemistry. PDT generates a large amount of reactive oxygen species with the help of sufficient oxygen, damaging the bacterial biological structure; magnetothermal action achieves physical sterilization and further enhances the effects of PDT and nanozymes; multiple nanozymes continuously inhibit bacterial activity from metabolic and defense levels. Through multi-target action, this system effectively combats... MRSA MDR E. coli It has a sterilization rate of over 99.7% and does not use antibiotics throughout the process, thus avoiding the development of drug-resistant bacteria from the root, with no drug residues and high biosafety.
[0026] In addition to its excellent antibacterial properties, the microneedles provided by this invention can also release Mg. 2+ It degrades excess lactic acid in wounds, improves local hypoxia, regulates immune cell function through multiple pathways, alleviates chronic inflammation in diabetic wounds, reshapes the immune microenvironment of wounds, and adapts to the repair needs of diabetic infected wounds.
[0027] The photomagnetic driven microalgae microneedle patch prepared by the method of this invention is soft and wearable. When combined with a portable light source and magnetic field device, it can be widely used in home care, field medical care, primary hospitals and other scenarios. It provides a brand-new "photo-magnetic-chemical" comprehensive treatment solution for skin and soft tissue infections caused by drug-resistant bacteria, and has extremely high clinical translational value and market application potential.
[0028] The technical solution of the present invention will be further described in detail below with reference to the accompanying drawings and embodiments. Attached Figure Description
[0029] Figure 1 The characterization results are those of the MFO powder prepared in Example 1 of this invention. in, Figure 1 In the image, 'a' is the SEM image of the MFO. Figure 1 In the diagram, b is the XRD pattern of the MFO. Figure 1 In the figure, c is the FTIR plot of MFO; Figure 2 These are the XPS test results of the MFO powder prepared in Example 1 of this invention; in, Figure 2 In the diagram, 'a' represents the XPS spectrum of the MFO. Figure 2 b in the figure represents the high-resolution peak fractionation spectrum of C 1s. Figure 2 c in the figure represents the high-resolution peak pattern of Mg1s. Figure 2 In the figure, d represents the high-resolution peak fractionation spectrum of O 1s. Figure 2 In the image, 'e' represents the high-resolution peak pattern of Fe 2p. Figure 3 The results are the magnetocaloric properties characterization results of the MFO powder prepared in Example 1 of this invention. Figure 4 These are the results of the photocatalytic performance characterization of the MFO powder prepared in Example 1 of this invention; Figure 5 These are the characterization results of the enzyme-like activity of the MFO powder prepared in Example 1 of this invention; in, Figure 5 In the diagram, 'a' represents the Nox-Like activity profile. Figure 5 In the diagram, b represents the MPO-Like activity profile. Figure 5 In the diagram, 'c' represents the LDH-Like activity profile. Figure 6 These are the structural characterization results of the MP nanomaterials of this invention; in, Figure 6 In the image, 'a' is a SEM image of the MP nanomaterials prepared in Example 2. Figure 6 In the diagram, b represents the XRD pattern of the MP nanomaterials prepared in Example 2. Figure 6 In the figure, c represents the zeta potential diagram of the MP nanomaterials prepared in Examples 2-4 and Comparative Example 1; Figure 7 These are the magnetocaloric performance characterization results of the MP nanomaterials prepared in Example 2 of this invention; Figure 8 These are the photocatalytic performance characterization results of the MP nanomaterials prepared in Example 2 of this invention; in, Figure 8 In this context, 'a' represents the magnetocaloric test under room temperature conditions. Figure 8 In the figure, b represents the magnetocaloric test at 37℃. Figure 8 In this context, 'c' represents the magnetocaloric test at 48℃. Figure 9 These are the characterization results of the enzyme-like activity of the MP nanomaterials prepared in Example 2 of this invention; in, Figure 9 In the figure, 'a' represents the Nox-Like activity at room temperature. Figure 9 b in the figure represents the Nox-Like activity at 37℃. Figure 9 In the figure, c represents the Nox-Like activity at 48℃. Figure 9 In the diagram, d represents the MPO-Like activity profile. Figure 9 In the diagram, 'e' represents the LDH-Like activity level. Figure 10 These are SEM images of Chlorella vulgaris and the CMP materials prepared in Examples 4-8 of this invention; in, Figure 10 In the image, 'a' represents the SEM image of Chlorella vulgaris. Figure 10 In the image, b is the SEM image of the CMP material prepared in Example 4. Figure 10 In the image, 'c' represents the SEM image of the CMP material prepared in Example 5. Figure 10 In this image, d represents the SEM image of the CMP material prepared in Example 6. Figure 10 In this image, 'e' represents the SEM image of the CMP material prepared in Example 7. Figure 10 f in the figure is the SEM image of the CMP material prepared in Example 8; Figure 11 This is a test result diagram of test example 9 of the present invention; in, Figure 11 In the figure, 'a' is the XRD pattern of the CMP material prepared in Example 7. Figure 11 In the image, b is the FTIR spectrum of the CMP material prepared in Example 7. Figure 11 In the diagram, 'c' represents the zeta potential of the CMP materials prepared in Examples 4-8. Figure 11 In the diagram, 'd' represents the oxygen production performance of Examples 4-8. Figure 11 In the diagram, 'e' represents the photosynthetic activity diagram of Examples 4-8; Figure 12 These are the characterization results of the magnetocaloric properties of the CMP materials obtained in Examples 4-8 of this invention; in, Figure 12 In this context, 'a' represents the magnetocaloric heating curves of the CMP materials prepared in Examples 4-8 at 20A AMF. Figure 12 In the figure, b represents the photosynthetic activity of the CMP materials prepared in Examples 4-8 under 20A AMF. Figure 13 These are the photocatalytic performance characterization results of the CMP material prepared in Example 7 of this invention; in, Figure 13 In the diagram, 'a' represents the UV-vis absorbance of the CMP material generating ·OH at room temperature. Figure 13 In the diagram, b represents the UV-vis absorbance of the CMP material at 37℃, showing the generation of ·OH. Figure 13 In the figure, c represents the UV-vis absorbance of ·OH generated by CMP material at 48℃; Figure 14 These are the characterization results of the enzyme-like activity of the CMP material prepared in Example 7 of this invention; in, Figure 14 In the figure, 'a' represents the Nox-Like activity at room temperature. Figure 14 b in the figure represents the Nox-Like activity at 37℃. Figure 14 In the figure, c represents the Nox-Like activity at 48℃. Figure 14 In the diagram, d represents the MPO-Like activity profile. Figure 14 In the diagram, 'e' represents the LDH-Like activity level. Figure 15 This is a SEM image of CMPH obtained in Example 9 of the present invention; in, Figure 15 In the image, 'a' represents the SEM image at 90K magnification. Figure 15 In the image, b represents the SEM image at a magnification of 120K. Figure 15 In this image, c represents the SEM image at a magnification of 150K. Figure 16 This is the force-displacement curve of CMPH obtained in Example 9 of the present invention; Figure 17 This is a test result diagram of test example 15 of the present invention; in, Figure 17 In the diagram, 'a' represents a schematic diagram of bacterial colonies on a plate. Figure 17 b in MRSA Bacterial survival rate results Figure 17 c in MDR E. coli Bacterial survival rate results; Figure 18 This is an in vitro p-AMPK immunofluorescence staining image of macrophages of CMPH prepared in Example 9 of this invention; Figure 19This is an in vitro H3K18la immunofluorescence staining image of CMPH macrophages prepared in Example 9 of this invention; Figure 20 This is a graph showing the in vivo therapeutic effect test results of CMPH prepared in Example 9 of the present invention; in, Figure 20 In the image, 'a' represents the infected wound images and wound accumulation maps on days 0, 3, 7, and 12. Figure 20 In the figure, 'b' represents the quantitative statistical analysis of the area of infected wounds on days 0, 3, 7, and 12. Figure 20 In the graph, 'c' represents the mouse body weight statistics from day 1 to day 12. Figure 20 In the diagram, d represents the colony plate smear images of infected wounds on days 0, 3, 7, and 12. Figure 21 This is a blood routine test result of a mouse blood sample 12 days after treatment according to the present invention; in, Figure 21 In this context, 'a' represents the WBC test result. Figure 21 In this context, 'b' represents the RBC test result. Figure 21 In this context, 'c' represents the HCT test result. Figure 21 In this context, d represents the PLT test result. Detailed Implementation
[0030] The present invention will be further described below with reference to the accompanying drawings and embodiments. Unless otherwise defined, the technical or scientific terms used in this invention should have the ordinary meaning understood by one of ordinary skill in the art to which this invention pertains. The features mentioned above or the features mentioned in the specific examples of this invention can be combined arbitrarily, and these specific embodiments are only used to illustrate the invention and are not intended to limit the scope of the invention.
[0031] Example 1 Preparation of MFO powder: (1) Add 40 mL of ethylene glycol to a 100 mL beaker, then add 1.7 mmol of magnesium chloride hexahydrate (MgCl2·6H2O), sonicate at 200 W for 10 min, then add 5 mmol of ferric chloride hexahydrate (FeCl3·6H2O), sonicate for 10 min, then add 3.6 g of urea, sonicate for 10 min, then add 2 mL of PEG (molecular weight 400), sonicate for another 10 min, and finally add 4 g of PVP-K30 (polyvinylpyrrolidone), sonicate for 4 h, then pour the mixed solution into a 100 mL Teflon autoclave, and react at 200 °C for 8 h; after the reaction is complete, cool naturally to room temperature, place the reaction system in a centrifuge, centrifuge at 10000 rpm for 10 min, wash the resulting black precipitate with distilled water and ethanol in sequence, and dry at 60 °C for 8 h to obtain MFO powder.
[0032] Test Example 1: Structural characterization of MFO powder: The MFO powder was observed using a scanning electron microscope, and its crystal structure and chemical bonds were analyzed and verified using X-ray diffraction (XRD) and Fourier transform infrared spectroscopy (FTIR), respectively. The results are as follows: Figure 1 As shown. From Figure 1 As can be seen, the MFO powder has a spherical structure with crystal sizes around 300 nm. From... Figure 1 b and Figure 1 c shows that the XRD patterns of the MFO powders correspond to the standard card of MgFe2O4 (JCPDS:01-088-1936) and have the corresponding chemical bonds.
[0033] MFO powder was detected by X-ray photoelectron spectroscopy (XPS), and the results are as follows: Figure 2 As shown. From Figure 2 As can be seen, the high-resolution O1s XPS spectrum shows that the MFO powder has two peaks, one at 531.4 eV and the other at 532.8 eV. The former can be identified as lattice oxygen of MFO, and the latter can be identified as oxygen vacancy (OV), which ultimately demonstrates the successful preparation of MFO.
[0034] Test Example 2: Characterization of the magnetocaloric properties of MFO powder: To confirm the relationship between the magnetocaloric effect and MFO concentration, MFO aqueous solutions with concentrations of 500 μg / mL, 1 mg / mL, 3 mg / mL, and 6 mg / mL were prepared using water as the solvent, with pure water as the control group. The concentrations were measured at (20 A, 1.6 mT). f Stimulation was performed for 10 minutes at a magnetic field strength of 498 kH (AMF). The real-time temperature of each solution was recorded every 1 minute using an infrared thermal imager (Fluke TiS75). The results are as follows: Figure 3 As shown.
[0035] from Figure 3 It can be seen that under the same parameter conditions, after 10 minutes of stimulation, the pure water control group could only raise the temperature to 29.4℃, while MFO at a concentration of 1000 μg / mL could raise it to 58.4℃. With increasing MFO concentration, the temperature rise rate within 10 minutes became increasingly faster. At an MFO aqueous solution concentration of 6 mg / mL, after 3 minutes of stimulation with AMF, the temperature could reach 92.4℃. This temperature far exceeds the safe and effective window for in vivo magnetothermal therapy, and there is no clinical reference value for further temperature testing. This demonstrates that MFO has excellent magnetothermal properties.
[0036] Test Example 3: Characterization of the photocatalytic performance of MFO powder: To test the types of ROS generated by MFO under 660nm laser irradiation, ·OH was quantitatively captured using an MB fluorescent probe. The results are as follows: Figure 4 As shown.
[0037] from Figure 4 As can be seen, after MFO was irradiated under a 660nm laser for 10 min, its peak values at 609nm and 664nm were detected using an ultraviolet-visible spectrometer with MB as a probe. A significant decrease in the peak values was observed, indicating that MFO irradiated under a 660nm laser for 10 min has the ability to generate ·OH reactive oxygen species. Therefore, the MFO powder prepared in Example 1 possesses photocatalytic properties.
[0038] Test Example 4: Characterization of the enzyme-like activity of MFO powder: Further investigation into the activities of various enzymes in MFO powder yielded the following results: Figure 5 As shown.
[0039] like Figure 5 As shown in Figure a, the Nox-Like activity of MFO in a NaAc-HAc buffer system at pH 5.5 was detected using UV-vis. The NADPH characteristic absorbance decay experiment confirmed that, compared to the PBS group where MFO was replaced with NaAc-HAc buffer, MFO efficiently consumed intracellular NADPH. Therefore, MFO exhibits Nox-Like enzyme activity at pH 5.5.
[0040] In the microenvironment unique to bacterial infection, which is weakly acidic and contains Cl... - In this system, MFO can efficiently catalyze the reaction of H2O2 and Cl within the system. - A redox reaction occurs, generating highly oxidizing HClO. The in-situ generated HClO can target bacterial intracellular proteins, directly oxidizing key functional amino acids such as methionine and cysteine, disrupting the spatial conformation of core metabolic enzymes such as GAPDH in bacteria, causing them to lose their normal catalytic activity, directly blocking the normal operation of bacterial glycolysis metabolic pathways, inhibiting the basic life metabolic activities of bacteria from the source, and achieving effective inhibition of bacterial proliferation; A PBS control group and an MFO group were established. MPO-Like activity was detected colorimetrically in a NaAc-HAc buffer system at pH 5.5. The 200 μL reaction system contained MFO, 1.6 M KCl, and 40 mM H₂O₂. After incubation at 37 °C for 10 min, DPD (N,N-diethyl-p-phenylenediamine) working solution and 10 mg / mL KI solution were added sequentially for color development. The PBS control group was established by replacing MFO with NaAc-HAc buffer. Quantitative analysis was achieved by detecting the absorbance at 515 nm. The results showed (…). Figure 5b) MFO exhibits MPO-like activity; LDH-Like activity can cause bacterial energy depletion by interfering with bacterial glycolysis. A PBS control group and an MFO group were established. The PBS control group consisted of BeyoLysis™ Buffer A for Metabolic Assay solution without MFO in the lactate dehydrogenase kit. The results of the lactate dehydrogenase kit assay clearly confirmed (…). Figure 5 c) MFO can reverse the normal lactate dehydrogenation reaction in bacteria, continuously catalyzing the conversion of lactate to pyruvate and reducing lactate content; studies have shown that this reverse catalytic process consumes a large amount of intracellular NAD+, which is essential for bacterial survival. + Coenzymes directly block key steps in glycolysis, disrupting the bacteria's main energy supply pathway.
[0041] Example 2 Preparation of MP nanomaterials (MFO powder to polyethyleneimine mass ratio 1:1): MFO powder was mixed with water and sonicated at 200W to obtain an MFO powder dispersion. The MFO powder dispersion was added dropwise to an aqueous solution of polyethyleneimine (the mass ratio of MFO powder to polyethyleneimine was 1:1). After sonication for 30 min, the mixture was placed in a shaker at 37℃ and centrifuged at 180 rpm for 24 h. The centrifuged product was washed with water and pre-frozen at -80℃ for 30 min. Then, it was freeze-dried in a freeze dryer at 0.1 Pa and -56℃ for 12 h to obtain MP nanomaterials.
[0042] Example 3 The process for preparing MP nanomaterials is basically the same as in Example 2, except that the mass ratio of MFO powder to polyethyleneimine is 1:2.
[0043] Comparative Example 1 The process for preparing MP nanomaterials is basically the same as in Example 2, except that the mass ratio of MFO powder to polyethyleneimine is 2:1.
[0044] Test Example 5: Structural characterization of MP nanomaterials: The MP nanomaterials prepared in Example 2 were observed using a scanning electron microscope, and their crystal structure was analyzed using an X-ray diffractometer (XRD).
[0045] The electronegativity of the MP nanomaterials prepared in Examples 2-3 and Comparative Example 1 was detected by nanoparticle size and zeta potential meter.
[0046] The above test results are as follows Figure 6 As shown, from Figure 6As can be seen, the MP nanomaterials prepared in Example 2 have the same morphology as MFO, appearing as spheres with a size of approximately 300 nm. From... Figure 6 b. As can be seen, the XRD pattern of the MP nanomaterials prepared in Example 2 corresponds to the standard cards (JCPDS: 01-088-1936) for MFO and MgFe2O4. Figure 6 c shows that when the mass ratio of PEI to MFO powder is 1:1, it can be converted to a positive charge of 5.72mV, which indicates that the MP modification was successful.
[0047] Test Example 6: Characterization of the magnetocaloric properties of MP nanomaterials: To confirm the magnetocaloric properties of MP nanomaterials after PEI surface coating, aqueous solutions of MP nanomaterials (using the MP nanomaterials prepared in Example 2) with concentrations of 200 μg / mL, 400 μg / mL, 600 μg / mL, 800 μg / mL, and 1000 μg / mL were prepared using water as the solvent. Pure water was used as a control group. The results were obtained at (20 A, 1.6 mT). f Stimulation was performed for 10 minutes at an AMF magnetic intensity of 498 kH. The real-time temperature of each solution was recorded every 1 minute using an infrared thermal imager. The results are as follows: Figure 7 As shown.
[0048] from Figure 7 It can be seen that under a 20A magnetic flux density (AMF) stimulation for 10 minutes, the water control group only reached a temperature of 29.3℃, while the MP aqueous solution at a concentration of 200 μg / mL reached 40.2℃. Furthermore, the temperature rise rate within 10 minutes increased with increasing MP content; at a solution concentration of 800 μg / mL, stimulation under AMF for 8 minutes resulted in a temperature of 48.6℃, demonstrating the excellent magnetocaloric properties of MP. Its magnetocaloric properties are comparable to those of MFO; at 1000 μg / mL, stimulation under AMF for 10 minutes resulted in a temperature of 57.9℃.
[0049] Test Example 7: Characterization of the photocatalytic performance of MP nanomaterials: The ability of an 800 μg / mL MP aqueous solution to generate ROS under 660 nm laser irradiation was tested, and ·OH was quantitatively captured using an MB fluorescent probe. The results are as follows: Figure 8 As shown.
[0050] from Figure 8As can be seen, when an 800 μg / mL MP aqueous solution was irradiated with a 660 nm laser for 10 min, and scanned every 2 min, the peak values at 609 nm and 664 nm were detected using MB as a fluorescent probe via UV-Vis. The peak values gradually decreased with increasing stimulation time, indicating that MP nanomaterials irradiated with a 660 nm laser for 10 min have the ability to generate ·OH reactive oxygen species. Figure 8 b、 Figure 8 Figure c shows the photocatalytic performance of 800 μg / mL MP under simulated magnetocaloric conditions at 37℃ and 48℃. It was found that the performance in generating ·OH was significantly improved at 48℃. Therefore, the prepared MP nanomaterials possess photocatalytic properties, and magnetocaloricity can enhance their photocatalytic performance.
[0051] Test Example 8: Characterization of enzyme-like activity of MP nanomaterials: The catalytic activities of various enzymes in MP nanomaterials were investigated, and the results are as follows: Figure 9 As shown (n=3, *** indicates) P <0.001).
[0052] Among them, such as Figure 9 As shown in Figure a, the characteristic absorbance decay experiment of NADPH confirms that MP nanomaterials can efficiently consume intracellular NADPH in bacteria, and can promote the activity of this type of enzyme under simulated heat stimulation at 37℃ and 48℃. Figure 9 b、 Figure 9 c) MPO-Like activity was detected colorimetrically in a NaAc-HAc buffer system at pH 5.5. A PBS control group and an MP group were established, with the MP group having its MP replaced by NaAc-HAc buffer. The results showed ( Figure 9 d) MP materials possess MPO-like activity; LDH-like activity was detected using a lactate dehydrogenase kit. A PBS control group and an MP group were established. The PBS control group consisted of BeyoLysis™ Buffer A for Metabolic Assay solution without MP, as specified in the lactate dehydrogenase kit. Results showed ( Figure 9 e), MP materials possess LDH-like activity.
[0053] Example 4 Preparation of CMP materials: The MP nanomaterials prepared in Example 2 were mixed with water to obtain an MP solution of 200 μg / mL; 1 mL of the 200 μg / mL MP solution and 1 mL of OD were then mixed. 680A Chlorella solution with a concentration of 1.0 was dispersed in a 15 mL centrifuge tube containing 8 mL of sterile water, for a total volume of 10 mL. The tube was then placed in a biochemical incubator and incubated at 37°C and 180 rpm in the dark for 60 min. Finally, it was centrifuged at 4800 rpm for 10 min to obtain the CMP material.
[0054] Example 5 The process of preparing CMP material is basically the same as in Example 4, except that the concentration of MP solution is 400 μg / mL.
[0055] Example 6 The process for preparing CMP material is basically the same as in Example 4, except that the concentration of MP solution is 600 μg / mL.
[0056] Example 7 The process of preparing CMP material is basically the same as in Example 4, except that the concentration of MP solution is 800 μg / mL.
[0057] Example 8 The process of preparing CMP material is basically the same as in Example 4, except that the concentration of MP solution is 1000 μg / mL.
[0058] Test Example 9: Structural characterization of CMP materials: The CMP materials prepared in Examples 4-8 were observed using a scanning electron microscope, and the results are as follows: Figure 10 As shown. From Figure 10 It can be seen that the 800 μg / mL MP solution is tightly loaded on Chl with a size of approximately 3 μm.
[0059] The CMP material prepared in Example 7 was analyzed using X-ray diffraction (XRD) and Fourier transform infrared spectroscopy. The results are shown in the figure. Figure 11 ( Figure 11 a and Figure 11 b) The CMP materials prepared in Examples 4-8 were analyzed using a zeta potentiometer, and the results are shown in the figure. Figure 11 ( Figure 11 c) The effects of different mass ratios on Chl activity during the preparation of CMP materials were investigated, and the results are shown in [Figure number missing]. Figure 11 ( Figure 11 d and Figure 11 e).
[0060] Figure 11 The XRD pattern of a shows that the characteristic peaks of CMP material are consistent with those of single-component nanomaterials, confirming the successful preparation of CMP material; Figure 11The FTIR of b showed that CMP possessed all the characteristic peaks of the single components compared to the individual components. Figure 11 c-nanoparticle size and zeta potential analysis showed that the electronegativity of the CMP material gradually decreased with increasing MP loading (MP solution concentration), further indicating the successful preparation of engineered microalgae. Figure 11 d and Figure 11 As shown in Figure e, Chl exhibits the strongest oxygen production and photosynthetic activity when the CMP loading is 800 μg (MP solution concentration 800 μg / mL), because Mg 2+ It is an essential element for Chl photosynthesis, and at appropriate concentrations, it significantly enhances photosynthetic activity and oxygen production capacity. MFO slowly releases Mg in the infection microenvironment. 2+ It directly supplies Chl to the load, maintains high chlorophyll content and photosynthetic activity, and ensures continuous oxygen production.
[0061] Test Example 10: Characterization of the magnetocaloric properties of CMP materials: The magnetocaloric properties of CMP materials with different MP loadings in Examples 4-8 were tested, such as... Figure 12 As shown in (a), 800 μg of MP was loaded onto Chl. At (20 A, 1.6 mT, f After stimulation with an AMF (498 kH) magnetic intensity for 10 min, the temperature reached 48 °C. Furthermore, the effect of magnetocaloric temperature on Chl photosynthetic activity under different MP loadings during CMP recombination was investigated. Figure 12 As shown in (b), the photosynthetic activity was strongest when stimulated with AMF for 8 min at a loading of 800 μg. Therefore, AMF stimulation for 8 min was chosen for subsequent experiments.
[0062] Test Example 11: Characterization of the photocatalytic performance of CMP materials: The photocatalytic performance of the CMP material prepared in Example 7 was detected by UV-vis, such as... Figure 13 As shown.
[0063] from Figure 13 As can be seen, after irradiating 800 μg of CMP with a 660 nm laser for 10 min, with scans every 2 min to detect its peak values at 609 nm and 664 nm, the peak values gradually decreased with increasing stimulation time. This indicates that CMP material irradiated with a 660 nm laser for 10 min has the ability to generate ·OH reactive oxygen species. Figure 13 b、 Figure 13Figure c shows the photocatalytic performance of 800 μg / mL CMP under simulated magnetocaloric conditions at 37 °C and 48 °C. It was found that the performance in generating ·OH was significantly improved at 48 °C. Therefore, the CMP materials prepared in Examples 4-8 possess photocatalytic properties, and magnetocaloricity can further enhance their photocatalytic performance.
[0064] Test Example 12: Characterization of enzyme-like activity of CMP materials: The catalytic activities of various enzymes in CMP materials were investigated, and the results are as follows: Figure 14 As shown (n=3, *** indicates) P <0.001).
[0065] Figure 14 The results show that the CMP material can efficiently consume intracellular NADPH, as confirmed by the NADPH characteristic absorbance attenuation experiment. Figure 14 b and Figure 14 c shows that simulated heat at 37℃ and 48℃ can promote the activity of this type of enzyme; MPO-Like activity was detected colorimetrically in a NaAc-HAc buffer system at pH 5.5. A PBS blank control group, a CMP group, and a CMP+AMF group were established (alternating magnetic field AMF for 8 min, magnetic field frequency was...). f =498kH, maximum magnetic field strength 1.6mT), where the PBS control group was formed by replacing CMP with NaAc-HAc buffer. The results showed ( Figure 14 d) CMP possesses MPO-like activity and can promote the activity of this type of enzyme under AMF stimulation; LDH-Like activity was detected using a lactate dehydrogenase kit. A PBS blank control group, a CMP group, and a CMP+AMF group were established (alternating magnetic field AMF for 8 min, magnetic field frequency was...). f =498kH, maximum magnetic field strength 1.6mT), PBS control group was BeyoLysis™ Buffer A for Metabolic Assay solution without CMP in the lactate dehydrogenase kit. Results showed ( Figure 14 e) CMP materials possess LDH-Like activity, and AMF stimulation can promote LDH-Like activity.
[0066] Example 9 Preparation of photomagnetically driven microalgae microneedle patches: Prepare 1 mL of 20% hyaluronic acid solution using sterile water. Then, place the CMP material obtained in Example 7 into the hyaluronic acid solution to obtain a CMPH solution. Inject 200 μL of the CMPH solution into the tip cavity of a polydimethylsiloxane (PDMS) microneedle mold. The reaction is evacuated three times, with each evacuation lasting 1 min followed by pressure holding for 3 min to remove air bubbles from the mold. The mold is then placed in a 37°C oven for 24 h to concentrate the CMPH solution, adding CMPH solution several times during this period until the final total system volume is 1 mL. The microneedles are then separated from the mold to obtain a photomagnetically driven microalgae microneedle patch, CMPH (Chl@MgFe2O3). 4-x / PEI-HA).
[0067] Comparative Example 2 Prepare 1 mL of 20% hyaluronic acid solution (HA solution) with sterile water. Take 200 μL of the prepared HA solution and inject it into the tip cavity of the polydimethylsiloxane (PDMS) microneedle mold. Vacuum the reaction three times, holding the vacuum for 3 minutes after each vacuuming for 1 minute to remove air bubbles from the mold. Then place it in an oven at 37°C for 24 hours to concentrate the HA solution. During this period, HA solution is added several times until the final total volume of the system is 1 mL. Separate the microneedles from the mold to obtain HA microneedle patches, denoted as HAMNs.
[0068] Test Example 13: Structural characterization and mechanical strength testing of CMPH: The morphological characteristics of CMPH were observed using SEM, such as... Figure 15 As shown.
[0069] from Figure 15 As can be seen, the CMPH array has a regular square structure with a side length of 8.9 mm, and is composed of 10×10 conical needles. Each needle is 800 μm long, 300 μm in diameter, and has a needle spacing of 650 μm.
[0070] In addition, to verify whether CMPH possesses the mechanical strength required to penetrate the stratum corneum, a universal testing machine was used for performance testing. Figure 16 As shown, the force-displacement curve flattens out at 42 N, indicating that the needle tip breaks and begins to exhibit inelastic deformation. The applied force of a single microneedle (0.42 N) far exceeds the 0.1 N threshold required for skin penetration, confirming that the material has transdermal delivery capabilities.
[0071] Test Example 14: In vitro antibacterial properties characterization of CMPH: The antibacterial properties of CMPH were evaluated using the plate coating method. Different antibacterial agents were selected... MRSA and MDR E. coliAs research subjects, the following groups were set up for the experiment: Control: PBS blank control group (bacteria, no materials, no stimulation), denoted as Group I; HA MNs + AMF + 660nm: Hyaluronic acid microneedle carrier group (HA MNs were prepared from Comparative Example 2, and stimulated with an alternating magnetic field AMF for 8 min, with a magnetic field frequency of ). f =498kH, maximum magnetic field strength is 1.6mT, current intensity is 20A; 660nm laser illumination for 10min, power is 0.5W / cm². 2 ), which is designated as Group II; CMPH: (materials only, without external magnetic field or light stimulation), designated as Group III; CMPH+660nm: CMPH microneedles + 660nm laser irradiation (660nm laser irradiation for 10 minutes, power 0.5W / cm²). 2 ), denoted as group IV; CMPH+AMF: CMPH microneedles + alternating magnetic field (alternating magnetic field AMF stimulation for 8 minutes, magnetic field frequency is...) f =498kH, maximum magnetic field strength is 1.6mT, current intensity is 20A), denoted as group V; CMPH+AMF+660nm: CMPH microneedles + AMF magnetic field + 660nm laser synergistic stimulation (alternating magnetic field AMF stimulation for 8 minutes, magnetic field frequency is...) f =498kH, maximum magnetic field strength is 1.6mT, current intensity is 20A; 660nm laser illumination for 10min, power is 0.5W / cm². 2 ), which is denoted as group VI.
[0072] The above test results are as follows Figure 17 As shown, the results indicate that 660nm laser irradiation and AMF stimulation had no significant effect on either bacterium without CMP. CMPH, constructed using CMP, showed significantly better inactivation effects on both bacteria than HA MNs under both single and dual stimulation. Furthermore, CMPH achieved an inactivation rate of 99.7% on both bacteria under the combined stimulation of 660nm laser irradiation and AMF, demonstrating broad-spectrum bactericidal activity against both Gram-positive and Gram-negative drug-resistant bacteria.
[0073] Test Example 15: In vitro anti-inflammatory potential test of CMPH: The activation effect of CMPH microneedle-mediated photomagnetic synergistic therapy on the AMPK signaling pathway was investigated using in vitro macrophage immunofluorescence staining. The following groups were specifically set up for the experiment: Control: PBS blank control group (bacteria, no materials, no stimulation), denoted as Group I; HA MNs + AMF + 660nm: Hyaluronic acid microneedle carrier group (HA MNs were prepared from Comparative Example 2, and the alternating magnetic field AMF stimulation was applied for 8 min with a magnetic field frequency of 1000 nm). f =498kH, maximum magnetic field strength is 1.6mT, current intensity is 20A; 660nm laser illumination for 10min, power is 0.5W / cm². 2 ), which is designated as Group II; CMPH: (materials only, without external magnetic field or light stimulation), designated as Group III; CMPH+660nm: CMPH microneedles + 660nm laser irradiation (660nm laser irradiation for 10 minutes, power 0.5W / cm²). 2 ), denoted as group IV; CMPH+AMF: CMPH microneedles + alternating magnetic field (alternating magnetic field AMF stimulation for 8 minutes, magnetic field frequency is...) f =498kH, maximum magnetic field strength of 1.6mT, current intensity of 20A) stimulus, denoted as group V; CMPH+AMF+660nm: CMPH microneedles + AMF magnetic field + 660nm laser synergistic stimulation (alternating magnetic field AMF stimulation for 8 minutes, magnetic field frequency is...) f =498kH, maximum magnetic field strength is 1.6mT, current intensity is 20A; 660nm laser illumination for 10min, power is 0.5W / cm². 2 ), which is denoted as group VI.
[0074] The above test results are as follows Figure 18 As shown, the p-AMPK fluorescence signal in macrophages was weak in the Control group and the HA MNs+AMF+660nm group; the p-AMPK expression level in the single CMPH, CMPH+660nm or CMPH+AMF treatment groups was only slightly upregulated; while in the CMPH+AMF+660nm photomagnetic synergistic treatment group, the red fluorescence intensity of p-AMPK was significantly enhanced and mainly located in the cytoplasm, indicating that the photomagnetic synergistic effect can effectively induce AMPK phosphorylation activation in macrophages, providing key signaling pathway evidence for subsequent regulation of macrophage polarization.
[0075] The regulatory effect of photomagnetic synergistic therapy on histone lactation modification in macrophages was investigated using immunofluorescence staining. Figure 19As shown, DAPI staining in each group revealed intact cell nuclei. In the Control group and each single treatment group, the fluorescence signal of H3K18la (lactation modification of lysine at position 18 of histone H3) in the macrophage nucleus was at a low level. However, in the CMPH+AMF+660nm combined treatment group, the red fluorescence intensity of H3K18la in the cell nucleus was significantly increased and highly colocalized with DAPI staining, suggesting that photomagnetic synergistic therapy can significantly induce lactation modification of histone H3K18 site in macrophages, revealing the potential mechanism of CMPH microneedles regulating the anti-inflammatory repair phenotype of macrophages from an epigenetic perspective.
[0076] Test Example 16: In vivo therapeutic effects of CMPH: To evaluate the promoting effects of CMPH on wound healing, anti-inflammation, and angiogenesis in MRSA-induced diabetic mice after infection, a full-thickness skin wound model was established, and the following groups were selected for the experiment: Control: PBS blank control group (bacteria, no materials, no stimulation), denoted as Group I; HA MNs + AMF + 660nm: Hyaluronic acid microneedle carrier group (HA MNs were prepared from Comparative Example 2, and stimulated with an alternating magnetic field AMF for 8 min, with a magnetic field frequency of ). f =498kH, maximum magnetic field strength is 1.6mT, current intensity is 20A; 660nm laser illumination for 10min, power is 0.5W / cm². 2 ), which is designated as Group II; CMPH: (materials only, without external magnetic field or light stimulation), designated as Group III; CMPH+660nm: CMPH microneedles + 660nm laser irradiation (660nm laser irradiation for 10 minutes, power 0.5W / cm²). 2 ), denoted as group IV; CMPH+AMF: CMPH microneedles + alternating magnetic field (alternating magnetic field AMF stimulation for 8 minutes, magnetic field frequency is...) f =498kH, maximum magnetic field strength of 1.6mT, current intensity of 20A) stimulus, denoted as group V; CMPH+AMF+660 nm: CMPH microneedles + AMF magnetic field + 660nm laser synergistic stimulation (alternating magnetic field AMF stimulation for 8 minutes, magnetic field frequency is...) f =498kH, maximum magnetic field strength is 1.6mT, current intensity is 20A; 660nm laser illumination for 10min, power is 0.5W / cm². 2 ), which is denoted as group VI.
[0077] The above results are as follows Figure 20As shown (n=3, *** indicates) P <0.001), indicating that the wound treatment method is as follows: one day before modeling (day -1), an in-situ injection is administered at the wound site. MRSA The suspension showed significant bacterial proliferation and suppuration at the wound site, indicating... MRSA A diabetic mouse model of infection was successfully established (day 0). Wound sites were recorded daily on days 0, 3, 7, and 12 to observe wound healing under different treatment conditions. Figure 20 As shown in Figure a, representative skin wound photographs on days 0, 3, 7, and 12 after treatment in different groups. On day 0, there was no significant difference in wound area among the different groups, indicating that the constructed full-thickness skin wounds were uniformly circular. As treatment progressed, by day 7, the CMPH+AMF+660nm group showed significant wound healing, demonstrating excellent antibacterial effects. The elimination of bacteria at the wound site greatly promoted wound healing and prevented wound infection and inflammation-induced healing stagnation. By day 12, the wounds in the CMPH+AMF+660nm group were almost completely healed, demonstrating that CMPH effectively promotes the proliferation and migration of damaged tissue in CMP-engineered microalgae, thereby promoting wound healing. (Overlay of wound area at different days...) Figure 20 This is also illustrated in b). This wound healing result demonstrates that CMPH possesses highly efficient bactericidal activity under 660nm laser irradiation, and that 20A, 8min AMF stimulation promotes cell proliferation and migration, thus accelerating wound healing. Based on statistical analysis of weight data during treatment, Figure 20 c. Mice initially experienced weight loss due to diabetes, but overall remained stable during treatment, indicating that CMPH had no toxic side effects on the mice's growth. Wound tissue samples were taken on days 3, 7, and 12 of treatment and homogenized for application to assess the in vivo antibacterial effect of CMPH. Figure 20 As shown in Figure d, on day 3 of treatment, compared with the control group, the HA MNs+AMF+660nm group still had a large number of bacterial colonies; CMPH exhibited certain antibacterial efficiency due to the multi-enzyme activity of CMP. On day 7 of treatment, compared with day 3, the number of bacterial colonies in the group irradiated with 660nm laser light was significantly reduced, indicating that CMPH has a highly effective in vivo anti-drug-resistant bacterial effect. On day 12 of treatment, the in vivo antibacterial efficiency of the CMPH+AMF+660nm group was significantly improved, and the wound healing rate of mice was significantly improved.
[0078] like Figure 21 a- Figure 21As shown in d, after 12 days of treatment, blood samples were collected from mice for routine blood tests. The levels of WBC, RBC, HCT, and PLT in the mice in the treatment group were all within the normal range, and the rate of inflammation reduction was faster than that in the control group, further demonstrating the safety of CMPH in vivo.
[0079] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention and not to limit them. Although the present invention has been described in detail with reference to preferred embodiments, those skilled in the art should understand that modifications or equivalent substitutions can still be made to the technical solutions of the present invention, and these modifications or equivalent substitutions cannot cause the modified technical solutions to deviate from the spirit and scope of the technical solutions of the present invention.
Claims
1. A method for preparing a photomagnetically driven microalgae microneedle patch, characterized in that, Includes the following steps: S1. Mix ethylene glycol, magnesium chloride hexahydrate, ferric chloride hexahydrate, urea, polyethylene glycol, and polyvinylpyrrolidone, and react to obtain MFO powder; S2. Mix MFO powder with water and add it to a polyethyleneimine solution. Sonicate the mixture. After sonication, incubate and centrifuge to obtain MP nanomaterials. S3. After mixing MP nanomaterials with water, an MP solution is obtained. Then, Chlorella solution and water are added, and the mixture is incubated and centrifuged to obtain CMP material. S4. Place the CMP material in a hyaluronic acid solution to obtain a CMPH solution. Then, add the CMPH solution to a microneedle mold and perform vacuuming and concentration in sequence to obtain a photomagnetically driven microalgae microneedle patch.
2. The method for preparing the photomagnetically driven microalgae microneedle patch according to claim 1, characterized in that, The volume molar ratio of ethylene glycol, magnesium chloride hexahydrate, and ferric chloride hexahydrate in S1 is 40 mL: 1.5~1.9 mmol: 4.5~5.5 mmol; The mass-to-volume ratio of urea to ethylene glycol is 3-4 g: 40 mL; The volume ratio of polyethylene glycol to ethylene glycol is 1.5~2.5:40; The mass-to-volume ratio of polyvinylpyrrolidone to ethylene glycol is 3.5~4.5g:40mL.
3. The method for preparing the photomagnetically driven microalgae microneedle patch according to claim 1, characterized in that, The reaction described in S1 is carried out at a temperature of 180~220℃ for 6~10h.
4. The method for preparing the photomagnetically driven microalgae microneedle patch according to claim 1, characterized in that, The mass ratio of MFO powder to polyethyleneimine in S2 is 1:1~2; The incubation temperature described in S2 is 36~38℃, the incubation time is 22~26h, and the oscillation frequency is 160rpm~200rpm.
5. The method for preparing the photomagnetically driven microalgae microneedle patch according to claim 1, characterized in that, The mass fraction of the MP solution mentioned in S3 is 200~1000 μg / mL; The OD of the Chlorella solution 680 The value is 0.5~2.0; The volume ratio of the MP solution to the Chlorella solution is 0.5~1.5:
1.
6. The method for preparing the photomagnetically driven microalgae microneedle patch according to claim 1, characterized in that, The incubation described in S3 is carried out under light-protected conditions, at a temperature of 36~38℃, for a time of 55~65min, and with an oscillation frequency of 160~200rpm.
7. The method for preparing the photomagnetically driven microalgae microneedle patch according to claim 1, characterized in that, The mass fraction of the hyaluronic acid solution in S4 is 15%~25%; The volume-to-mass ratio of the hyaluronic acid solution to the CMP material is 1 mL: 200~1000 μg.
8. The method for preparing the photomagnetically driven microalgae microneedle patch according to claim 1, characterized in that, The number of vacuuming operations described in S4 is ≥3 times, and the process of a single vacuuming operation is as follows: vacuuming for 0.5~1.5 min and holding for 2.5~3.5 min; The concentration is carried out at a temperature of 36-38°C for 22-26 hours.
9. A photomagnetically driven microalgae microneedle patch prepared by the preparation method according to any one of claims 1 to 8.
10. The application of the photomagnetically driven microalgae microneedle patch according to claim 9 in the preparation of a medical dressing for treating diabetic wounds.